脐带延迟结扎和脐带挤压输血对早产儿脑血流动力学的影响：一项随机双盲对照试验 (Zhongguo Dang Dai Er Ke Za Zhi, 2021)
OBJECTIVE: To compare the effect of delayed cord clamping (DCC) versus umbilical cord milking (UCM) on cerebral blood flow in preterm infants. METHODS: This was a single-center, prospective, double-blind, randomized controlled trial. A total of 46 preterm infants, with a gestational age of 30-33(+6) weeks, who were born in Suining Central Hospital from November 2, 2018 to November 15, 2019 were enrolled and randomly divided into DCC group and UCM group, with 23 infants in each group. The primary outcome indexes included cerebral hemodynamic parameters[peak systolic velocity (PSV), end-diastolic velocity (EDV), and resistance index (RI)] measured by ultrasound within 0.5-1 hour, (24±1) hours, (48±1) hours, and (72±1) hours after birth. Secondary outcome indexes included hematocrit, hemoglobin, red blood cell count, and serum total bilirubin levels on the first day after birth and the incidence rate of intraventricular hemorrhage during hospitalization. RESULTS: A total of 21 preterm infants in the DCC group and 23 in the UCM group were included in the statistical analysis. There was no significant difference in PSV, EDV, and RI between the two groups at all time points after birth (P > 0.05). There was also no significant difference between the two groups in the hematocrit, hemoglobin, red blood cell count and total bilirubin levels on the first day after birth, and the incidence rate of intraventricular hemorrhage during hospitalization (P > 0.05). CONCLUSIONS: DCC and UCM have a similar effect on cerebral hemodynamics in preterm infants with a gestational age of 30-33(+6) weeks.